Persuasive Communication Practices of Engineers in Cross-Boundary Decision-Making. Issue 3 (2nd September 2022) - Coso Strong, Alexandra; Stockman, Tehya; Heale, Tom; Meyer, Steven; Meyerson, Elena
ABSTRACT: Engineers rely on communication skills to collaborate and make decisions across boundaries. This research seeks to examine an under-explored communication practice of engineers in work environments – persuasive communication. Research on persuasive communication (i.e. practices seeking to influence) includes extensive explorations within laboratory settings and certain contexts (e.g. healthcare, politics), yet should be further expanded within the engineering context. Using a multiple case study approach, we explored engineers' communication practices across three organizations as they sought to negotiate, build consensus, persuade, and make decisions across boundaries. Engineers within this study commonly used persuasive communication to gain access to resources, align goals, and influence design decisions. These practices are presented through three narratives constructed based on the analysis of interviews and meeting observations as well as a rich understanding of the context. The narratives illustrate six emergent features of persuasive communication: (1) emotional engagement, (2) credibility of those involved, (3) audience consideration and power dynamics, (4) timing, (5) adaptability, and (6) shared situation awareness. These results highlight the pervasiveness of persuasive communication within engineering practice, providing a foundation for future work. The findings also have implications for supporting the development of engineering students and early career engineers.